USM LECTURER RECEIVES INTERNATIONAL AWARD IN EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
KUBANG KERIAN, 7 December 2016 – A lecturer from the Universiti Sains Malaysia (USM) Health Campus has made the university proud by winning an international award on the use of effective teaching methodologies to facilitate students’ learning.